Discourse Analysis (DA) in the Context of English as a Foreign Language (EFL): A Chronological Review - Derin, Tatum; Susilo Putri, Nunung; Nursafira, Mutia Sari; Hamuddin, Budianto (Elsya : Journal of English Language Studies, 2020)
This current study is interested in assessing the trending studies discourse analysis during the last five years in the specific context of English as a Foreign Language (EFL). Using the library research method, this study collected 131,000 results of relevant articles from Google Scholar open-access database. This study then analysed 40 selected articles as its main data with NVivo 12 software to ensure its qualitative. Chronologically, this study described how discourse analysis studies have evolved. At first, solely focusing on using discourse analysis to identify students’ problems in reading comprehension, researchers began to use discourse analysis to examine how teachers authentically perform and propose ways to improve the classroom discourse. Moreover, discourse analysis not only revealed issues that exist between teacher-student and student-student interactive discourses, but also the discourse of critical issues contained in the textbooks that are mandated for EFL programmes.